Comparison of Dual- and Single-Source Dual-Energy CT for Diagnosis of Acute Pulmonary Artery Embolism - Petritsch, Bernhard; Pannenbecker, Pauline; Weng, Andreas Max; Veldhoen, Simon; Grunz, Jan-Peter; Bley, Thorsten Alexander; Kosmala, Aleksander (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose Comparison of dual-source dual-energy CT (DS-DECT) and split-filter dual-energy CT (SF-DECT) regarding image quality and radiation dose in patients with suspected pulmonary embolism.Materials and Methods We retrospectively analyzed pulmonary dual-energy CT angiography (CTPA) scans performed on two different CT scanners in 135 patients with suspected pulmonary embolism (PE). Scan parameters for DS-DECT were 90/Sn150 kV (n = 68 patients), and Au/Sn120 kV for SF-DECT (n = 67 patients). The iodine delivery rate was 1400 mg/s in the DS-DECT group vs. 1750 mg/s in the SF-DECT group. Color-coded iodine distribution maps were generated for both protocols. Objective (CT attenuation of pulmonary trunk [HU], signal-to-noise ratio [SNR], contrast-to-noise ratio [CNR]) and subjective image quality parameters (two readers [R], five-point Likert scale), as well as radiation dose parameters (effective radiation dose, size-specific dose estimations [SSDE]) were compared.Results All CTPA scans in both groups were of diagnostic image quality. Subjective CTPA image quality was rated as good or excellent in 80.9 %/82.4 % (R1 / R2) of DS-DECT scans, and in 77.6 %/76.1 % of SF-DECT scans. For both readers, the image quality of split-filter iodine distribution maps was significantly lower (p < 0.05) with good or excellent ratings in only 43.3 %/46.3 % (R1 / R2) vs. 83.8 %/88.2 % for maps from DS-DECT. The HU values of the pulmonary trunk did not differ between the two techniques (p = n. s.), while both the SNR and CNR were significantly higher in the split-filter group (p < 0.001; p = 0.003). Both effective radiation dose (2.70 ± 1.32 mSv vs. 2.89 ± 0.94 mSv) and SSDE (4.71 ± 1.63 mGy vs. 5.84 ± 1.11 mGy) were significantly higher in the split-filter group (p < 0.05).Conclusion The split-filter allows for dual-energy imaging of suspected pulmonary embolism but is associated with lower iodine distribution map quality and higher radiation dose.Key points: Citation Format
Keywords: CT-angiography; dual-energy; pulmonary embolism; image quality; radiation dose